ANALISIS YURIDIS TERHADAP PEMBERIAN HAK PISTOLE BAGI TERPIDANA BUKAN KURUNGAN DALAM LEMBAGA PEMASYARAKATAN DI INDONESIA - Zainal Bahri; Erdianto Erdianto; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The law is expected to be able to protect the rights that should be given tocitizens who are carrying out the imprisonment criminal liability process. Thispunishment of imprisonment is also a form of crime of deprivation of liberty, butthis punishment of confinement is lighter in some respects than imprisonment.Similar to imprisonment, imprisonment is also a crime in the form of limiting thefreedom of movement of a convict which is carried out by closing that person in acorrectional institution. There are privileges for convicts who carry outimprisonment, convicts have gun rights, namely at their own expense they can seekconveniences for their lives while in correctional institutions, for example takingcare of food and or sleeping equipment through correctional officers In theCriminal Code (KUHP), the right to a gun is emphasized in Article 23 which reads:“A person in prison may improve his fate at his own expense.This research is included in the category of normative legalresearch/approach. Namely research that is focused on examining the applicationof the rules or norms in positive law. In collecting data for normative legalresearch, the library research method is used which includes studies by reviewing,analyzing and analyzing information obtained from various literature such asbooks, legislation, scientific papers, the internet and other sources, in terms of Inthis case, a researcher is required to be observant and precise in finding data thatis related to the subject matter.The author concludes that, the granting of Pistole rights or special rights isa right owned by a prison convict in the form of certain facilities; for example abed, or own food and medicine. Pistole rights are only owned by convicts in prison,while those who are sentenced to prison terms do not have that right. And 2.Regarding the obstacles faced in law enforcement granting gun rights to convictsin social confinement, namely: the human resource factor, the lack of facilitiesfactor and the community's legal awareness factor.Keyword : Provision, Gun right, Confinement.